An adjusted forward curve for spot rate forecasting - Sarmiento, Camilo (Science PG, 2020)
In this paper, we provide adjustments for liquidity and credit risk to the forward Libor rate in order to improve accuracy of the forward rate in forecasting the 3-month Libor rate. In particular, we introduce the adjusted forward curve (AFC) that models the update in the forward curve from one period to the next. A direct modeling of the dynamic process of the forward curve facilitates the specification of adjustment factors to the forward curve, and it underscores the role of mean reversion (stationarity) in the nexus between the forward rate and the future spot rate. The AFC factors that underpin the forward curve bias are statistically relevant with p-values that are less than .00001. The upward bias in the forward curve (i.e., when the forward curve exceeds the expected future spot rate) positively correlates with the steepness of the yield curve in the AFC model. A downward bias positively correlates with the credit spread and industrial capacity utilization. Furthermore, the effect of the instantaneous forward curve on the future spot rate tempers off with time. The predictive power of the AFC model, however, hinges on the forecastability of the underlying factors. The testing indicates that all the AFC model factors have a mean reversion component. Overall, our model effectively anticipates movements in the forward curve that tend to yield a better forecast of the future spot rate.

En este documento, proporcionamos ajustes por riesgo de liquidez y crédito a la tasa Libor a plazo para mejorar precisión del tipo forward al pronosticar el tipo Libor a 3 meses. En particular, introducimos la curva adelantada ajustada. (AFC) que modela la actualización en la curva forward de un periodo al siguiente. Un modelado directo del proceso dinámico de La curva directa facilita la especificación de factores de ajuste a la curva directa y subraya el papel de la media. reversión (estacionariedad) en el nexo entre el tipo forward y el tipo spot futuro. Los factores de la AFC que sustentan la El sesgo de la curva directa es estadísticamente relevante con valores de p inferiores a 0,00001. El sesgo alcista en la curva a plazo (es decir, cuando la curva a plazo excede la tasa spot futura esperada) se correlaciona positivamente con la pendiente de la curva de rendimiento en el Modelo AFC. Un sesgo a la baja se correlaciona positivamente con el diferencial de crédito y la utilización de la capacidad industrial. Además, el El efecto de la curva forward instantánea sobre el tipo de cambio spot futuro se atenúa con el tiempo. El poder predictivo de la AFC Sin embargo, el modelo depende de la previsibilidad de los factores subyacentes. Las pruebas indican que todos los factores del modelo AFC tienen un componente de reversión a la media. En general, nuestro modelo anticipa efectivamente movimientos en la curva a plazo que tienden a ceder una mejor previsión del tipo de cambio al contado futuro.
Keywords: Crédito; Credit; Riesgo (Economía); Risk; Tasas de interés; Interest rates; Adjusted Forward Curve; Forecasting Spot Rate; Yield Curve Steepness; Credit Risk; Mean Reversion; Curva adelantada ajustada; Pronóstico de tasa al contado; Pendiente de la curva de rendimiento; Riesgo crediticio; Reversión media